The Paradox of Dual Jurisdiction: Reassessing the Sharia Court in Aceh’s Special Autonomy Framework - Utang Rosidin; Jumhadi Jumhadi; Dendy Arifianto; Faly Antary Musaad; Mohamad Ichsana Nur (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2026)
The Aceh Sharia Court is the only judicial institution in Indonesia formally placed within two judicial environments simultaneously, i.e., the religious and general courts as stipulated in Article 3 A (2) of Law No. 50 of 2009. This dual placement creates a constitutional paradox that conflicts with Article 24(2) of the 1945 Constitution and Article 27(1) of Law No. 48 of 2009. While the former mandates a unified judicial system, the later prohibits special courts from being placed in more than one judicial environment. This research aims to analyze why the dual jurisdiction of the Sharia Court leads to a constitutional inconsistency and to formulate a normative reconstruction of its institutional position within Indonesia’s judicial system. Doctrinal legal research with conceptual, statutory, analytical, and comparative approaches was employed and combined with grammatical, systematic, and teleological methods of legal interpretation. The primary legal materials included the 1945 Constitution, Laws No. 11 of 2006, No. 48 of 2009, and No. 50 of 2009, supplemented by secondary doctrinal and scholarly sources. The study found that the dual jurisdiction constituted a fundamental constitutional inconsistency arising from an unresolvable horizontal conflict between two statutes of equal rank enacted in the same year, rendering the lex specialis and lex posterior principles inapplicable. It was concluded that the most optimal reconstruction was to reposition the Sharia Court as a sui generis special court singularly within the religious court environment, comprehensively regulated by a standalone organic statute. In this way, the Aceh’s special autonomy could still be preserved without sacrificing the constitutional coherence of Indonesia’s national judicial system.